Traumatic avulsion of the globe and optic nerve in a road traffic accident - Verma, Ritesh; Rathi, Manisha; Sachdeva, Sumit; Dhull, C. S.; Phogat, Jitender (International Journal Of Community Medicine And Public Health, 2017)
Road traffic accident is one of the important causes of ocular trauma. There is a need for strict traffic rules in third world countries where a majority of people travel on two wheelers and that too without a helmet. People generally tend to over speed or try to fit in their children on a two wheeler in our country. In this case report, we present a case of complete avulsion of eye ball and optic nerve in a patient of a road traffic accident. There are no documented cases of avulsion of the globe and optic nerve due to a road traffic accident in the available literature.